Fitness of three strains of alga Chromera velia Salinity and pH - Kabeláčová, Kateřina (Jihočeská univerzita, 2018)
This bachelor thesis demonstrates the ecological fitness of the alga C. velia and its three strains in different pH and salinity. Lipidomic analysis together with statistical analyses revealed significant differences among tested C. velia strains. Lipidic profile of all three strains was affected rather with salinity than pH level.
Fitness of three strains of alga Chromera velia Salinity and pH
Keywords: Chromera velia; autotrophy; heterotrophy; parasitism; fitness; cultivation; fatty acids; biotechnology